2016
DOI: 10.1097/01.epx.0000483165.56114.d8
|View full text |Cite
|
Sign up to set email alerts
|

Integron-mediated multidrug resistance in extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolated from fecal specimens in Egypt

Abstract: ESBL-producing E. coli and K. pneumoniae showed a marked degree of antibiotic resistance in both hospitalized and nonhospitalized study groups. The high prevalence of class 1 and 2 integrons among isolates of both groups has a serious impact on the spread of antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
5
1
1
Order By: Relevance
“…In contrary to what reported about the association of Int III with GES gene [49], current results showed that they coexist only in one isolate out of seven Int III positive isolates. Additionally, IMP gene coexisted with Int III in 42.9% of isolates which was unlike the study conducted by Elsherif et al who reported that Int III is of low occurrence with IMP gene [49].…”
Section: Plos Onecontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrary to what reported about the association of Int III with GES gene [49], current results showed that they coexist only in one isolate out of seven Int III positive isolates. Additionally, IMP gene coexisted with Int III in 42.9% of isolates which was unlike the study conducted by Elsherif et al who reported that Int III is of low occurrence with IMP gene [49].…”
Section: Plos Onecontrasting
confidence: 99%
“…Rezai et al reported that Int I was detected in 79.3% while Int II was harbored by 10.3% of isolates [48]. ESBL-producers were significantly associated with Int I (P = 0.033), similar to what reported by Elsherif et al, as Int 1 was associated with CTX-M gene (P = 0.039) [49]. In contrary to what reported about the association of Int III with GES gene [49], current results showed that they coexist only in one isolate out of seven Int III positive isolates.…”
Section: Plos Onesupporting
confidence: 75%
See 2 more Smart Citations
“…Enteropathogenic E. coli (EPEC), diffuse-adhering E. coli (DAEC) and enteroaggregative E. coli (EAEC) are associated with infantile diarrhea in Egyptian children where 220 enteroadherent E. coli were identified from 729 diarrheic children [ 64 ]. In another study, E. coli was isolated from 52.1% hospitalized patients and 60.4% from outpatient clinics with high degrees of resistance to ciprofloxacin and co-trimoxazole [ 65 ]. Also, there is increasing incidence of carbapenemase- and extended-spectrum β-lactamase-producing Enterobacteriaceae in dairy farms and hospital-acquired infections.…”
Section: Bacterial Zoonosismentioning
confidence: 99%